2003
DOI: 10.1016/s0042-6822(03)00315-5
|View full text |Cite
|
Sign up to set email alerts
|

Peach latent mosaic viroid variants inducing peach calico (extreme chlorosis) contain a characteristic insertion that is responsible for this symptomatology

Abstract: The involvement of Peach latent mosaic viroid (PLMVd) in an extensive chlorosis of peach known as calico (PC) has been advanced but ultimate proof is lacking. Sequencing of 16 full-length PLMVd cDNA clones of a PC isolate revealed two groups of variants. Nine had a size (336-338 nt) similar to that of typical PLMVd variants of nonsymptomatic and mosaic-inducing isolates, whereas the other 7 were longer (348-351 nt) due to an insertion of 12-13 nt. This insertion was always found in the hairpin loop capping the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0
23

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(116 citation statements)
references
References 42 publications
6
87
0
23
Order By: Relevance
“…PLMVd, usually a 335-339-long nucleotide (nt), is a typical species of the genus Pelamoviroid (family Avsunviroidae). Cloning and sequencing of PLMVd variants of asymptomatic and mosaic-inducing peach isolates have revealed a wide range of variants with sizes between 335 and 351 nt (Pelchat et al, 2000;Malfitano et al, 2003). PLMVd does not have a central conserved region (CCR) and has acquired selfcleaving properties by forming hammerhead ribozyme structures (Flores & Llácer, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…PLMVd, usually a 335-339-long nucleotide (nt), is a typical species of the genus Pelamoviroid (family Avsunviroidae). Cloning and sequencing of PLMVd variants of asymptomatic and mosaic-inducing peach isolates have revealed a wide range of variants with sizes between 335 and 351 nt (Pelchat et al, 2000;Malfitano et al, 2003). PLMVd does not have a central conserved region (CCR) and has acquired selfcleaving properties by forming hammerhead ribozyme structures (Flores & Llácer, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Se han descrito infecciones viroidales en plantas herbáceas y leñosas así como en plantas dicotiledóneas y monocotiledóneas. (Reanwarakorn y Semancik, 1998;Malfitano et al 2003).…”
Section: Gama De Huéspedesunclassified
“…Most studies on viroid pathogenesis have been undertaken with PSTVd, the type species of the family Pospiviroidae, or with Peach latent mosaic viroid (Malfitano et al, 2003) and Chrysanthemum chlorotic viroid (De la as representative members of the family Avsunviroidae. In PSTVd, sequence variations related to symptom severity have been essentially mapped to the P domain (Schnölzer et al, 1985;Owens et al, 1991Owens et al, , 1995Owens et al, , 1996, but more recent reports have shown that the left and right terminal domains, as well as a single substitution in the loop E within the C domain, also contribute to symptom expression .…”
Section: Short Communicationmentioning
confidence: 99%
“…Estudios paralelos con miembros de la familia Avsunviroidae han revelado distorsiones en cloroplastos y presencia de cuerpos membranosos en las regiones cloróticas de hojas infectadas con el ASBVd, mientras que en hojas totalmente cloróticas se observan lo que parecen ser proplastidios alterados en vez de cloroplastos (Desjardins, 1987). Esta última observación ha sido reproducida en hojas infectadas con el PLMVd, algunas de cuyas variantes inducen una clorosis extrema (cálico), que en los casos más agudos cubre toda la superficie foliar (Malfitano et al, 2003;Rodio et al, 2006 Rodio et al, y 2007.…”
Section: Movimiento a Larga Distanciaunclassified
“…Estudios paralelos con miembros de la familia Avsunviroidae han revelado distorsiones en cloroplastos y presencia de cuerpos membranosos en las regiones cloróticas de hojas infectadas con el ASBVd, mientras que en hojas totalmente cloróticas se observan lo que parecen ser proplastidios alterados en vez de cloroplastos (Desjardins, 1987). Esta última observación ha sido reproducida en hojas infectadas con el PLMVd, algunas de cuyas variantes inducen una clorosis extrema (cálico), que en los casos más agudos cubre toda la superficie foliar (Malfitano et al, 2003;Rodio et al, 2006 Rodio et al, y 2007.También existen importantes diferencias en cuanto a la gama de huéspedes. Un caso extremo lo constituyen los viroides de la familia Avsunviroidae cuyo espectro se restringe a una sola o a un grupo reducido de especies próximas, mientras que otros viroides como el HSVd colonizan multitud de especies distintas, produciendo tanto enfermedades como infecciones latentes (Shikata, 1990;.…”
unclassified